Response and resistance in 300 patients with BCR-ABL-positive leukemias treated with imatinib in a single center - Lahaye, Tanja; Riehm, Birte; Berger, Ute; Paschka, Peter; Müller, Martin Christian; Kreil, Sebastian; Merx, Kirsten; Schwindel, Uwe; Schoch, Claudia; Hehlmann, Rüdiger; Hochhaus, Andreas (Cancer, 2005)
BACKGROUND The advent of imatinib has considerably changed the treatment of chronic myeloid leukemia (CML). Early studies demonstrated high rates of hematologic and cytogenetic responses in all phases of the disease after limited observation periods. METHODS The authors evaluated long-term outcome, rates of response, and resistance in 300 patients with BCR-ABL-positive leukemias (CML in chronic phase after failure to respond to interferon-alpha [CP], n = 139; accelerated phase [AP], n = 80; myeloid blast crisis [BC], n = 76; lymphoid BC and Philadelphia chromosome-positive acute lymphoblastic leukemia, n = 5) who entered clinical trials with imatinib in a single center after an observation time of 4.5 years. RESULTS In CP, hematologic remission was achieved in 97% and major (MCR) and complete cytogenetic remission (CCR) in 61% and 49% of patients, respectively. The chance to achieve MCR was higher in patients commencing imatinib earlier in the course of CML. In AP, the median survival period after the start of imatinib was 44 months, and MCR and CCR were observed in 31% and 26% of patients, respectively. In myeloid BC, the median survival period after the start of imatinib and after diagnosis of BC was 6 and 9 months, respectively. Hematologic resistance occurred in 25%, 41%, and 92% of patients in CP, AP, and myeloid BC, respectively, and was associated with BCR-ABL mutations in 45% of patients and with clonal evolution in 58% of patients. CONCLUSIONS The data emphasized the need for a prolonged follow-up of patients treated with imatinib to define the clinical potential of the drug and to establish methods to optimize therapy.
Gesehen am 11.05.2022